2013
DOI: 10.1103/physrevlett.110.070601
|View full text |Cite
|
Sign up to set email alerts
|

Bold Diagrammatic Monte Carlo Method Applied to Fermionized Frustrated Spins

Abstract: We demonstrate, by considering the triangular lattice spin-1/2 Heisenberg model, that Monte Carlo sampling of skeleton Feynman diagrams within the fermionization framework offers a universal first-principles tool for strongly correlated lattice quantum systems. We observe the fermionic sign blessing-cancellation of higher order diagrams leading to a finite convergence radius of the series. We calculate the magnetic susceptibility of the triangular-lattice quantum antiferromagnet in the correlated paramagnet re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
74
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 33 publications
2
74
0
1
Order By: Relevance
“…Convergence of the skeleton diagrammatic series to an unphysical branch rather than its divergence in difficult regimes is a critical result for a wealth of analytic and numeric approaches, especially in light or the substantial recent interest in methods based on explicit summation of skeleton diagrams [9,[25][26][27]. It reveals a generic scenario of breaking down of skeleton expansions, in which there is no a priori indication of the series becoming untrustworthy.…”
Section: The Use Of Functionals ω[G] φ[G] σ[G]mentioning
confidence: 99%
“…Convergence of the skeleton diagrammatic series to an unphysical branch rather than its divergence in difficult regimes is a critical result for a wealth of analytic and numeric approaches, especially in light or the substantial recent interest in methods based on explicit summation of skeleton diagrams [9,[25][26][27]. It reveals a generic scenario of breaking down of skeleton expansions, in which there is no a priori indication of the series becoming untrustworthy.…”
Section: The Use Of Functionals ω[G] φ[G] σ[G]mentioning
confidence: 99%
“…It can stochastically evaluate the integrals and the different topologies occurring in higher-order perturbation theory and thus provide an answer to the question posed above. It has previously been applied to various fermionic problems such as the unitary Fermi gas 15 , Anderson localization 16 , the Hubbard model in the Fermi-liquid regime 17 , and frustrated-spin systems 18,19 . For the unitary Fermi gas and the three-dimensional (3D) Fermi-polaron problem it was found that the full many-body answer is very close to the first-order result given by a hole line on top of a T matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Major recent achievements of DiagMC are the study of the normal phase of the unitary fermi gas [13], the determination of the ground state phase diagram of the Hubbard model up to filling factor 0.7 and interactions U/t ≤ 4 [14], and the settlement of the Bose-metal issue [15]. Given the power and the versatility of the technique, systematic diagrammatic extensions of Dynamical Mean Field Theory are now being studied [16,17].In DiagMC [10,11,18,19] one expresses the perturbative expansion in terms of connected Feynman diagrams, which can be written directly in the TL. One then performs a random walk in the space of topologies and of integration variables of Feynman diagrams.…”
mentioning
confidence: 99%
“…In DiagMC [10,11,18,19] one expresses the perturbative expansion in terms of connected Feynman diagrams, which can be written directly in the TL. One then performs a random walk in the space of topologies and of integration variables of Feynman diagrams.…”
mentioning
confidence: 99%